IMPLEMENTATION OF USER CENTERED DESIGN METHOD ON WEB-BASED STOCK APP - Mutiara Br Samosir; Volvo Sihombing; Rahmadani Pane (Jurnal Mantik, 2022)
The increasing growth of technology necessitates that business professionals have particular, realistic, and actual data processing information systems as well as the confidence to operate within their human limitations. A strong data processing system has a significant impact on the formal and informal success of an organization. Therefore, the researcher aims to design and develop a web-based stock application utilizing the UCD (User-Centered Design) methodology and design modeling with UML (Unified Modeling Language), the most effective tool for object-oriented system development. The researcher employs the UCD approach because it is a method for designing and creating systems that place the users at the centre of the application creation and design process. In this study, the researcher collects data by identifying problems, conducting a literature review, and distributing questionnaires to assess user requirements. With a weighted score of 5 for respondents who strongly agree, 4 for respondents who agree, 3 for respondents who are neutral, 2 for respondents who do not agree, and 1 for respondents who strongly disagree, the results of the questionnaire are presented utilizing a Likert scale to measure a person's perspective, attitudes, and perceptions of an event. Thus, the program was developed in accordance with user requirements and is usable.